Cannabis Greenhouse Management System with IOT Technology - Siraphop Tooprakai; Rujiphat Thanbumrung Pimlaphat Panaworn; Peerawit Samrit (My University, 2024)
This paper presents the cannabis greenhouse management system with IOT technology. The cannabis cultivation control system consists of 2 parts: controlling the environment inside the greenhouse and displaying various statuses in the greenhouse such as temperature, humidity and light, etc.
Keywords: IoT-based Smart Home Systems; Smart Agriculture and AI